Solvent-Induced Lag Phase during the Formation of Lysozyme Amyloid Fibrils Triggered by Sodium Dodecyl Sulfate: Biophysical Experimental and In Silico Study of Solvent Effects - Gabriel Zazeri; Ana Paula Ribeiro Povinelli; Nathália Mariana Pavan; Alan M. Jones; Valdecir Farias Ximenes (Molecules, 2023)
Amyloid aggregates arise from either the partial or complete loss of the native protein structure or the inability of proteins to attain their native conformation. These aggregates have been linked to several diseases, including Alzheimer’s, Parkinson’s, and lysozyme amyloidosis. A comprehensive dataset was recently reported, demonstrating the critical role of the protein’s surrounding environment in amyloid formation. In this study, we investigated the formation of lysozyme amyloid fibrils induced by sodium dodecyl sulfate (SDS) and the effect of solvents in the medium. Experimental data obtained through fluorescence spectroscopy revealed a notable lag phase in amyloid formation when acetone solution was present. This finding suggested that the presence of acetone in the reaction medium created an unfavorable microenvironment for amyloid fibril formation and impeded the organization of the denatured protein into the fibril form. The in silico data provided insights into the molecular mechanism of the interaction between acetone molecules and the lysozyme protofibril, once acetone presented the best experimental results. It was observed that the lysozyme protofibril became highly unstable in the presence of acetone, leading to the complete loss of its β-sheet conformation and resulting in an open structure. Furthermore, the solvation layer of the protofibril in acetone solution was significantly reduced compared to that in other solvents, resulting in fewer hydrogen bonds. Consequently, the presence of acetone facilitated the exposure of the hydrophobic portion of the protofibril, precluding the amyloid fibril formation. In summary, our study underscores the pivotal role the surrounding environment plays in influencing amyloid formation.